A Survey of Load Balencing Technique in Cloud Computing Environment (International Journal of Engineering and Computer Science, 2016)
Cloud computing refers to service delivery over internet by several application which are in distributed data centers. Cloud computing has many advantages along with some issues. These issues are related with load management, reliability, data portability, various security issues and much more. In this paper our main concern is load balancing algorithms in cloud computing. The load can be network load, memory capacity, CPU load etc. The load balancing is a process of reassigning the total load to the individual nodes of the collective system to make resource utilization effective and to improve the response time of the job, simultaneously removing a condition in which some of the nodes are over loaded while some others are under loaded. This paper presents various issues of cloud computing especially related to load balancing and various load balancing algorithms or technique in cloud computing adopted in past research work have been analyzed and findings were illustrated in this paper.